Fabrication and antimicrobial analysis of composite biodegradable film from yam starch - Siti Nur Farahana, Ismail (2010)
The purpose of this study is to produce biocomposite packaging film which is environmental friendly in nature and have potential to be used in the food packaging industry application. The objectives of this study are to fabricate different types of composite biodegradable film from yam starch and analyse antimicrobial activities of the films in resistance to Escherichia coli and Bacillus subtilis. Other than that, the films were characterized in term of physical and chemical properties. In this study, the biodegradable film will be fabricated with addition of antimicrobial agent to lead complete degradation process. Chitosan is used ad antimicrobial agent. The film preparation is by mix the yam flour with 1% acetic acid, chitosan, PEG 400 and water. Then, from the solution produced, the film is casted on the glass plate and left at ambient temperature until it has become dry. The film was then peeled from the glass plate after the drying is complete. The film is characterized by using fourier transform infrared (FT-IR) spectra, scanning electron microscope (SEM), antimicrobial activity, water solubility and viscosity. From the result, Fourier Transform Infrared (FT-IR) spectra analysis revealed starch crystallinity and hydrogen bonds were formed between chitosan and starch at wavelength 400-4000cm-1. For water solubility, the film containing 3% chitosan only have 34.9578 % water solubility compared to film that containing 1% chitosan have 59.2309 % water solubility. Films containing 3% chitosan is also showed it has the highest viscosity value, which is 1413 cP at 20 rpm. From antimicrobial test, the result showed that, the more chitosan is used, the lower the colony to breed.